LINC00473‐modified bone marrow mesenchymal stem cells incorporated thermosensitive PLGA hydrogel transplantation for steroid‐induced osteonecrosis of femoral head: A detailed mechanistic study and validity evaluation. Issue 2 (8th December 2021) - Xu, Yingxing; Jiang, Yaping; Wang, Yingzhen; Jia, Bin; Gao, Song; Yu, Haiyang; Zhang, Haining; Lv, Chengyu; Li, Haiyan; Li, Tao
Abstract: The pathogenesis of steroid‐induced osteonecrosis of the femoral head (SONFH) involves a glucocorticoid‐induced imbalance of osteogenic and adipogenic differentiation, and apoptosis of bone marrow mesenchymal stem cells (BMSCs). An increasing number of genes, especially noncoding RNAs, have been implicated in the function of BMSCs. Our previous studies have confirmed the key role of LINC00473 and miR‐23a‐3p on the osteogenic, adipogenic differentiation, and apoptosis of BMSCs. However, the underlying mechanism of this process is still unclear. Based on bioinformatics analysis, here we investigated the effects of LINC00473 on the LRP5/Wnt/β‐catenin signaling pathway in the osteogenesis and adipogenesis of BMSCs, as well as the PEBP1/Akt/Bad/Bcl‐2 signaling pathway in dexamethasone‐ (Dex‐) induced apoptosis of BMSCs. Our data showed that LINC00473 could promote osteogenesis and suppress the adipogenesis of BMSCs through the activation of the miR‐23a‐3p/LRP5/Wnt/β‐catenin signaling pathway axis, while rescuing BMSCs from Dex‐induced apoptosis by activating the miR‐23a‐3p/PEBP1/Akt/Bad/Bcl‐2 signaling pathway axis. Notably, we observed that LINC00473 interacted with miR‐23a‐3p in an Argonaute 2 (AGO2)‐dependent manner based on dual‐luciferase reporter assay, AGO2‐related RNA immunoprecipitation, and RNA antisense purification assay. Furthermore, injectable thermosensitive polylactic‐co‐glycolic acid (PLGA) hydrogel loaded with rat‐derived BMSCs (rBMSCs) modified by LINC00473 were used for the treatment of SONFH in a rat model. Our results demonstrated that PLGA hydrogels provided a suitable environment for harboring rBMSCs. Besides, transplantation of PLGA hydrogels loaded with rBMSCs modified by LINC00473 could significantly promote the bone repair and reconstruction of the necrotic area at the femoral head in our SONFH rat model. Surprisingly, compared with the transplantation of BMSCs alone, the transplanted rBMSCs encapsulated within the PLGA hydrogel could migrate from the medullary cavity to the femoral head. In summary, LINC00473 promoted osteogenesis, inhibited adipogenesis, and antagonized Dex‐induced apoptosis of BMSCs. Therefore, LINC00473 could provide a new strategy for the treatment of SONFH.